2022
DOI: 10.3390/v14091911
|View full text |Cite
|
Sign up to set email alerts
|

Virus Diversity, Abundance, and Evolution in Three Different Bat Colonies in Switzerland

Abstract: Bats are increasingly recognized as reservoirs for many different viruses that threaten public health, such as Hendravirus, Ebolavirus, Nipahvirus, and SARS- and MERS-coronavirus. To assess spillover risk, viromes of bats from different parts of the world have been investigated in the past. As opposed to most of these prior studies, which determined the bat virome at a single time point, the current work was performed to monitor changes over time. Specifically, fecal samples of three endemic Swiss bat colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…In accordance with the study objectives, bacteriophage sequences were not investigated further. Encountering bacterial virus sequences is common in studies of chiropteran viromes [ 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the study objectives, bacteriophage sequences were not investigated further. Encountering bacterial virus sequences is common in studies of chiropteran viromes [ 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primates have additional TRIM duplications on chromosome 11 close to the TRIM5/6/22/34 cluster, including TRIM49 and 64 ( 120 ). Bats host many types of viruses ( 123 125 ) and have duplications of TRIM5 and 22 ( 107 , 126 ). There are other species-specific differences of C-IV members in bats, including duplications of TRIM25, 41, 60, and 75 ( 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…This means that the host usually carries a low viral load and is able to tolerate some viral replication. Studies have shown that bats have unique immunological approaches to enable coexistence with viral infections, causing no disease, while allowing enough viral replication for transmission (30)(31)(32). Screening the virome for over 4000 healthy bats from 40 different species of both Yangochiroptera and Yinpterochiroptera suborders, revealed an array of viruses belonging to diverse families, the most prevalent being Herpesviridae, Papillomaviridae, Retroviridae, Adenoviridae and Astroviridae, but also Coronaviridae, Caliciviridae, Polyomaviridae, Rhabdoviridae, among others (33), confirming bats as reservoirs of various virus.…”
Section: Divergence Analysismentioning
confidence: 99%